2007
DOI: 10.1300/j371v15n03_04
|View full text |Cite
|
Sign up to set email alerts
|

Medication Errors in Community/Ambulatory Care:

Abstract: This study was to develop estimates of the incidence, severity, and cost of medication errors and to evaluate strategies for reducing medication errors relevant to community/ambulatory care from published literatures. Relevant studies and reviews that assessed medication errors or medication safety were identified through MEDLINE, manual literature search of reference list and recommendations. Studies in peer-reviewed journals from 1995-2005 and earlier major studies were inclued.• Interface between care setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 76 publications
1
4
0
Order By: Relevance
“…The most frequently reported drug errors found in our study originated from drug prescribing. This finding is consistent with findings from other studies conducted in the intensive and ambulatory care settings. The most commonly reported prescribing drug error was prescribing a wrong drug (Table ).…”
Section: Discussionsupporting
confidence: 93%
“…The most frequently reported drug errors found in our study originated from drug prescribing. This finding is consistent with findings from other studies conducted in the intensive and ambulatory care settings. The most commonly reported prescribing drug error was prescribing a wrong drug (Table ).…”
Section: Discussionsupporting
confidence: 93%
“…Prescribing errors are the most frequently reported ambulatory medication errors in the published literature 17. Within prescribing, the most commonly reported medication error in our study was related to medication dose.…”
Section: Discussionmentioning
confidence: 54%
“…From these 19 systematic reviews, three (Kuo , Pepper & Towsley , Voshall et al . ) were found to be methodologically weak (AMSTAR < 5) and were subsequently excluded.…”
Section: Search Strategymentioning
confidence: 99%
“…From these 19 systematic reviews, three (Kuo 2006, Pepper & Towsley 2007, Voshall et al 2013) were found to be methodologically weak (AMSTAR < 5) and were subsequently excluded. A total of 16 reviews ranging from high to medium quality were eligible for inclusion, including four each from Australia (Hodgkinson et al 2006, Manias et al 2012, 2014, Raban & Westbrook 2014; and the United Kingdom (Conroy et al 2007, Wimpenny & Kirkpatrick 2010, Alsulami et al 2012, Keers et al 2014; two each from the United States (Gonzales 2010, Ohashi et al 2014; and Netherlands (D€ uckers et al 2009(D€ uckers et al , Maaskant et al 2015; and one each from Canada (Wulff et al 2011); Germany (Hopkinson & Jennings 2013); Ghana (Acheampong et al 2014) and Sweden (Kullberg et al 2013).…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation